2009
DOI: 10.1111/j.1365-2958.2009.06624.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk between two global regulators in Streptomyces: PhoP and AfsR interact in the control of afsS, pstS and phoRP transcription

Abstract: SummaryThe regulatory proteins AfsR and PhoP control expression of the biosynthesis of actinorhodin and undecylprodigiosin in Streptomyces coelicolor. Electrophoretic mobility shift assays showed that PhoP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 48 publications
(130 reference statements)
1
114
0
3
Order By: Relevance
“…More than 117 genes were up-or downregulated in an afsS disruption mutant (136). Disruption of afsS also causes diminished actinorhodin production during phosphate starvation, an observation underpinned by the finding that AfsR and PhoP bind to overlapping sequences in the promoter region of afsS (82). Although AfsS is usually thought of as a regulator of antibiotic biosynthetic genes, transcriptome analysis showed that it also has major effects on nutritional starvation genes, which might possibly be responsible for the effects on antibiotic production (136).…”
Section: The Afsk/afsr/afss System and A Possible Interface With Hyphmentioning
confidence: 90%
See 2 more Smart Citations
“…More than 117 genes were up-or downregulated in an afsS disruption mutant (136). Disruption of afsS also causes diminished actinorhodin production during phosphate starvation, an observation underpinned by the finding that AfsR and PhoP bind to overlapping sequences in the promoter region of afsS (82). Although AfsS is usually thought of as a regulator of antibiotic biosynthetic genes, transcriptome analysis showed that it also has major effects on nutritional starvation genes, which might possibly be responsible for the effects on antibiotic production (136).…”
Section: The Afsk/afsr/afss System and A Possible Interface With Hyphmentioning
confidence: 90%
“…Some reported observations are hard to explain. For example, PhoP binds to, and represses, the promoter of afsS, encoding a global activator of antibiotic production (82). This negative effect is counterintuitive since phosphate limitation activates production of ACT and RED, an effect mediated by enhanced transcription of the relevant biosynthetic genes.…”
Section: Phosphate Regulation Of Antibiotic Production In S Coelicolormentioning
confidence: 99%
See 1 more Smart Citation
“…PhoP was found to bind a PHO box overlapping with the sequence recognized by AfsR. 36,37 Both PhoP and AfsR are positive regulators and compete for this sequence. Indeed, the affinity of AfsR for this PHO box is higher than that of PhoP, and therefore, PhoP interferes with optimal AfsR-mediated afsS expression.…”
Section: Phop Control Of Antibiotic and Other Secondary Metabolites Bmentioning
confidence: 99%
“…The first direct connection of the PhoP regulator with the control of antibiotic biosynthesis was made by Santos-Beneit et al 36 when they proved that PhoP binds the same sequence in the afsS promoter as the cognate-regulator AfsR. AfsS is a small protein (63 amino acid) that activates expression of actII-orf4 and redD, the cluster situated regulators of the actinorhodin and undecylprodigiosine biosynthetic clusters.…”
Section: Phop Control Of Antibiotic and Other Secondary Metabolites Bmentioning
confidence: 99%